Increased Na(+)-dependent D-glucose transport and altered lipid composition in renal cortical brush-border membrane vesicles from bile duct-ligated rats. - Y Imai; JE Scoble; N McIntyre; JS Owen (Journal of Lipid Research, 1992)
Erythrocyte membranes of patients with liver disease are characteristically enriched in cholesterol, a change known to impair several carrier-mediated membrane transport functions. In the present study we have assessed whether experimental liver disease can affect the membrane lipid composition and transport function of kidney epithelial cells. Small (about 5%) but significant (P less than 0.01) increases were found in the cholesterol-to-phospholipid molar ratio (C/PL) of rat renal cortical brush-border membrane (BBM) vesicles 3, 8, and 15 days after bile duct ligation which correlated closely with increased fluorescence polarization, i.e., decreased membrane fluidity (r = 0.75, P less than 0.001; n = 27). A lipoprotein-mediated pathogenesis was suggested by the close relationship between BBM C/PL and plasma C/PL (r = 0.69, P less than 0.001). The mean high-affinity Na(+)-coupled D-glucose uptake by BBM vesicles was higher 1, 3, 8, and 15 days after ligation than in non-operated rats, significantly so at 3 and 8 days (611 +/- 37 and 593 +/- 22 vs. 507 +/- 21 pmol/mg protein per 4 sec; P less than 0.05), and was positively correlated with BBM C/PL (r = 0.58, P less than 0.01) and fluorescence polarization (r = 0.41, P less than 0.05). Brief incubation of BBM vesicles from normal rats with cholesterol-rich phospholipid liposomes simultaneously increased BBM C/PL and Na(+)-dependent D-glucose uptake. Stimulation of BBM Na(+)-glucose cotransport in ligated rats was not due to delayed dissipation of the Na+ gradient or to a more rapid development of membrane potential. High-affinity Na(+)-dependent D-glucose uptake kinetics in 3-day bile duct-ligated rats showed a lower Kt, without an alteration in maximum velocity, Vmax, compared to sham-operated animals (0.298 +/- 0.015 vs. 0.382 +/- 0.029 mM; P less than 0.05), whilst the binding dissociation constant, Kd of high-affinity phlorizin binding sites was reduced by ligation (0.453 +/- 0.013 vs. 0.560 +/- 0.015 microM; P less than 0.001). We conclude that an early effect of bile duct ligation is to enrich renal cortical brush-border membranes in cholesterol, thereby decreasing membrane fluidity and stimulating Na(+)-dependent D-glucose uptake by increasing the affinity of the carrier.